Functional recovery after surgical resection of low grade gliomas in eloquent brain: hypothesis of brain compensation. Issue 7 (1st July 2003) - Duffau, H; Capelle, L; Denvil, D; Sichez, N; Gatignol, P; Lopes, M; Mitchell, M-C; Sichez, J-P; Van Effenterre, R
Abstract : Objectives: To describe functional recovery after surgical resection of low grade gliomas (LGG) in eloquent brain areas, and discuss the mechanisms of compensation. Methods: Seventy-seven right-handed patients without deficit were operated on for a LGG invading primary and/or secondary sensorimotor and/or language areas, as shown anatomically by pre-operative MRI and intraoperatively by electrical brain stimulation and cortico-subcortical mapping. Results: Tumours involved 31 supplementary motor areas, 28 insulas, 8 primary somatosensory areas, 4 primary motor areas, 4 Broca's areas, and 2 left temporal language areas. All patients had immediate post-operative deficits. Recovery occurred within 3 months in all except four cases (definitive morbidity: 5%). Ninety-two percent of the lesions were either totally or extensively resected on post-operative MRI. Conclusions: These findings suggest that spatio-temporal functional re-organisation is possible in peritumoural brain, and that the process is dynamic. The recruitment of compensatory areas with long term perilesional functional reshaping would explain why: before surgery, there is no clinical deficit despite the tumour growth in eloquent regions; immediately after surgery, the occurrence of a deficit, which could be due to the resection of invaded areas participating (but not essential) to the function; and why three months after surgery, almost complete recovery had occurred. This brain plasticity, which decreases the long term risk of surgical morbidity, may be used to extend the limits of surgery in eloquent areas.